Aerosol assisted chemical vapor deposition of Sb2S3 thin films: Environmentally benign solar energy material. (December 2015) - Murtaza, Ghulam; Akhtar, Masood; Azad Malik, Mohammad; O'Brien, Paul; Revaprasadu, Neerish
Abstract: Antimony sulfide (Sb2 S3, stibnite) is an important environmentally benign material which finds applications in solar cells, thermoelectric devices, switching devices, microwaves and television cameras. Orthorhombic (stibnite) Sb2 S3 thin films have been deposited by Aerosol-Assisted Chemical Vapor Deposition (AACVD), spin coating, melt and the doctor's blade methods using tris (thiobenzoato)antimony(III) complex as a single source precursor. The p-XRD pattern of thin films deposited by all the methods show the deposition of Sb2 S3 (stibnite). The morphology of the films is typically based on sheets, thick plates or bundles of sticks with varying sizes depending on the technique used and/or the deposition temperature. The EDX analysis showed that the films deposited at all temperatures by all methods are antimony rich. The band gaps of the films deposited by AACVD range from 1.81 to 1.90 eV.